2018
DOI: 10.1021/acs.inorgchem.8b01599
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Ligand Cooperativity Promoting Sulfur Atom Transfer in Ferrous Complexes and Isolation of a Sulfurmethylenephosphorane Adduct

Abstract: The reaction of elemental sulfur with the cis-divacant octahedral complex [(pyrrpy)Fe(OEt)] (1; pyrrpy = 3,5-Bu-bis(pyrrolyl)pyridine) yields the iron dimer [(pyrr-1-S-pyrrpy)Fe] (2; pyrr-1-S-pyrrpy = 3,5-(Bu-pyrrolyl)(1-S-3,5-Bu-pyrrolyl)pyridine) resulting from a pyrrpy ligand based S-oxidation of one pyrrole arm. Addition of the phosphorus ylide HCPPh to 1 forms the ylide adduct [(pyrrpy)Fe(CHPPh)] (3), which upon reaction with elemental sulfur produces a rare example of a sulfurmethylenephosphorane adduct,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 35 publications
(64 reference statements)
0
32
0
Order By: Relevance
“…In addition to imido formation upon exposure to organic azides, the Fe II starting material ( tBu PDP tBu )Fe(OEt 2 ) can engage in small molecule activation while retaining cis ‐divacant octahedral geometries in the corresponding products. This is exemplified by its reaction with elemental sulfur [10] and formation of a dinuclear bridging dinitrogen complex upon reduction with KC 8 [11] . Similar cis ‐divacant octahedral geometries were established in cobalt chemistry for ( tBu PDP tBu )Co(OEt 2 ) and the isolable organic azide adduct ( tBu PDP tBu )Co(N 3 1 Ad) [12] .…”
Section: Introductionmentioning
confidence: 63%
“…In addition to imido formation upon exposure to organic azides, the Fe II starting material ( tBu PDP tBu )Fe(OEt 2 ) can engage in small molecule activation while retaining cis ‐divacant octahedral geometries in the corresponding products. This is exemplified by its reaction with elemental sulfur [10] and formation of a dinuclear bridging dinitrogen complex upon reduction with KC 8 [11] . Similar cis ‐divacant octahedral geometries were established in cobalt chemistry for ( tBu PDP tBu )Co(OEt 2 ) and the isolable organic azide adduct ( tBu PDP tBu )Co(N 3 1 Ad) [12] .…”
Section: Introductionmentioning
confidence: 63%
“… 54 73 Because H 2 PDP proligands are prepared in a modular fashion, the corresponding PDP 2– ligands are well suited for the manipulation of specific steric and electronic profiles of coordinated metals. With this in mind, researchers have leveraged PDP metal complexes in catalysis, 50 atom and group transfer, 56 , 57 , 61 and photochemistry. 64 68 Despite this expanding wealth of research, PDP compounds of either lanthanide or actinide elements have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the solid-state structure, two cis -divacant octahedral [( t Bu pyrr) 2 py]Fe units are bridged through a dinitrogen molecule taking on the pseudo-axial position (Figure , right), whereas, on the other hand, cation−π interactions take place between potassium ions and two pyrrole units of two opposing ligands, enforcing the two ( t Bu pyrr) 2 py 2− ligands in an almost perfectly eclipsed orientation with a torsion angle of ∠(N py FeFeN py′ ) = 2.04(5)°, in a formal cis -arrangement with respect to the μ-N 2 ligand (Figure , left and middle). Complex 2 ·3­(C 7 H 8 ) (structure 2a ) crystallizes in the monoclinic space group C 2/ c , with a C 2 axis relating the two halves of the molecule in which a cis -divacant octahedral geometry around iron can be clearly observed (Figure , right). , Further inspection of the asymmetric unit shows one potassium binding to one pyrrole in an η 5 -fashion. Notably, alkali cation intercalation has also been shown to play a role within a series of iron, cobalt, and nickel dinitrogen complexes, influencing the degree of dinitrogen activation due to the electrostatic side-on interaction with the reduced μ-N 2 n – ligand, as well as the structural distortion of the respective complexes based on the change in ionic radius. Particular interest in the role of alkali cations in dinitrogen activation with iron relates of course to the H-B process, where potassium, other alkali or alkali-earth salts are known to be catalyst promoters. , In the case of 2 , the K + /pyrrolide interactions push the Fe atoms closer to a (nonbonded) distance of d (Fe–Fe) = 4.634(1) Å, which, in turn, displaces the dinitrogen unit from the idealized linear FeNNFe topology generally observed in most dinuclear iron dinitrogen complexes, such as type B depicted in Scheme ( vide supra ).…”
Section: Resultsmentioning
confidence: 99%
“…This ligand has been demonstrated to enforce constrained geometries, including an unusual cis- divacant octahedral coordination sphere in different oxidation and spin states, while also engaging in reversible redox reactions through its redox non-innocent character. , One-electron reduction of the monomeric cis -divacant octahedral bis­(pyrrolyl)­pyridine iron­(II) ether complex [( t Bu pyrr 2 py)­Fe­(OEt 2 )] ( 1 ) in toluene yields the dinuclear, distorted end-on μ-N 2 complex [K] 2 [( t Bu pyrr 2 py)­Fe] 2 (μ 2 -η 1 :η 1 -N 2 ) ( 2 ) that is connected through dinitrogen coordination as well as mutual η 5 -cation-π coordination of two potassium ions with four pyrrolyl units. In this arrangement, the unusual cis -divacant octahedral coordination mode around the iron ion is retained, with the dinitrogen ligand being displaced off the iron–iron vector, hence adopting form E with a resemblance to the α-type coordination in the H-B process.…”
Section: Introductionmentioning
confidence: 99%